Governança e coordenação em cadeias agroindustriais : um estudo da cadeia agroindustrial da carne bovina - Silva, Carlos Rodrigues da (2007)
The proposal of study of this paper searched to understand as the coordination and the governance can influence in the competitive dynamics of a representative of the processing segment of the agro-industrial chain of beef. The theoretical upport identified to aspects of governance and coordination as competitive strategy; it included characteristics on production chain, chain of value and supply chain; it approached aspects on the chain of agro-industrial production - in this context, they had been detached characteristic specific on the chain of production of the beef. The research methodology used was the qualitative, fore grounded, essentially, in the case study of a company who acts in the processing segment ox chain, where the examination of the collected material was implemented through the content analysis. As result was verified that the JBS-Friboi group, that represents the processing segment in this chain, acts of form to determine the actions of other members of the chain. Governance aspects had been identified in the relation between the processor and the cattle farming, once the processor imposes the standards for the production of the cattle. Coordination aspects in such a way in the relation with the producer as in the relations with the deliverer are observed, who if identifies through the negotiations for resolution of the conflicts.